Sustainable Diets and Biodiversity - Burlingame, Barbara; Dernini, Sandro (bioversity international, 2010)
ct It is time to face the evidence of a worldwide unsustainable food system. Its complexity makes it extremely fragile to any climatic, socio-economic, political or financial crisis. Thus, we urgently need appropriate understanding and new strategies to really accommodate present and future population needs and well-being. In that context, we need sustainable diets, with low-input, local and seasonal agro-ecological food productions as well as shortdistance production-consumption nets for fair trade. Cultural heritage, food quality and culinary skills are other key aspects determining sustainable dietary patterns and food security. Nutrition education about appropriate food choices remains essential everywhere. It thus appears very urgent to profoundly change our food strategy and to promote fair, culturally-appropriated, biodiversity-based, ecofriendly, sustainable diets. Authorities should urgently assume their responsibilities by orienting and supporting the appropriate and sustainable foodstuff productions and consumptions in all parts of the world.
Directions and Solutions for Policy, Research and Action
Keywords: biodiversity; diet; food; nutrition; behaviour challenge